Genetics of Degenerative Diseases - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Chromosome studies of four neurodegenerative diseases are described in current literature: Huntington disease cases in Finland show linkage disequilibrium of chromosome 4rflp haplotypes